PENERAPAN REGRESI COX PROPORTIONAL HAZARD UNTUK MENDUGA FAKTOR-FAKTOR YANG MEMENGARUHI LAMA MENCARI KERJA - SUDANA, I GEDE ARI; SUCIPTAWATI, NI LUH PUTU; IDA HARINI, LUH PUTU (E-Jurnal Matematika; Vol 2 No 3 (2013)DO - 10.24843/MTK.2013.v02.i03.p041, 2013)
Survival analysis is a statistical method that accommodates the collection of censored data . One of popular method in survival analysis is the Cox Proportional Hazard Regression . The Cox Proportional Hazard Regression can be used to see old looking for work where data may contain censored data . This article aim s investigate the characteristics of job seekers and the variables that affect old looking for work. To establish the best model us ing Stepwise Selection method. Prior to that the assumption of Cox Proportional Hazards Regression is tested using log minus log curve . The results obtained from Cox Proportional Hazards Regression model is as follows
Keywords: Survival analysis, Cox proportional hazard regression, old looking for work, unemployment